In memoriam: Dr. Juergen Karl Willmann - Editorial Office, Quant Imaging Med Surg (Quantitative Imaging in Medicine and Surgery; Vol 8, No 8 (September 30, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
We are extremely sad to know the passing of Professor Juergen Karl Willmann (Figure 1). Professor Dr. Juergen Karl Willmann died in a car accident on Jan 8 this year at the rather young age of 45 years old. Dr. Juergen Karl Willmann served as an associate editor of our journal shortly after this journal was founded in late 2011, and made significant contributions to the development of this journal. His passing is a tremendous loss to everyone.